Impact of older age in patients receiving atezolizumab and bevacizumab for hepatocellular carcinoma. (2nd September 2022) - Vithayathil, Mathew; D'Alessio, Antonio; Fulgenzi, Claudia A. M.; Nishida, Naoshi; Schönlein, Martin; von Felden, Johann; Schulze, Kornelius; Wege, Henning; Saeed, Anwaar; Wietharn, Brooke; Hildebrand, Hannah; Wu, Linda; et al.
Abstract: Background and Aims: Combination atezolizumab/bevacizumab is the gold standard for first‐line treatment of unresectable hepatocellular carcinoma (HCC). Our study investigated the efficacy and safety of combination therapy in older patients with HCC. Methods: 191 consecutive patients from eight centres receiving atezolizumab and bevacizumab were included. Overall survival (OS), progression‐free survival (PFS), overall response rate (ORR) and disease control rate (DCR) defined by RECIST v1.1 were measured in older (age ≥ 65 years) and younger (age < 65 years) age patients. Treatment‐related adverse events (trAEs) were evaluated. Results: The elderly ( n = 116) had higher rates of non‐alcoholic fatty liver disease (19.8% vs. 2.7%; p < .001), presenting with smaller tumours (6.2 cm vs 7.9 cm, p = .02) with less portal vein thrombosis (31.9 vs. 54.7%, p = .002), with fewer patients presenting with BCLC‐C stage disease (50.9 vs. 74.3%, p = .002). There was no significant difference in OS (median 14.9 vs. 15.1 months; HR 1.15, 95% CI 0.65–2.02 p = .63) and PFS (median 7.1 vs. 5.5 months; HR 1.11, 95% CI 0.54–1.92; p = .72) between older age and younger age. Older patients had similar ORR (27.6% vs. 20.0%; p = .27) and DCR (77.5% vs. 66.1%; p = .11) compared to younger patients. Atezolizumab‐related (40.5% vs. 48.0%; p = .31) and bevacizumab‐related (44.8% vs. 41.3%; p = .63) trAEs were comparable between groups. Rates of grade ≥3 trAEs and toxicity‐related treatment discontinuation were similar between older and younger age patients. Patients 75 years and older had similar survival and safety outcomes compared to younger patients. Conclusions: Atezolizumab and bevacizumab therapy is associated with comparable efficacy and tolerability in older age patients with unresectable HCC.